ChemInform Abstract: One‐Pot, Catalyst‐Free, Facile, and Efficient Sulfenylation of Electron‐Rich Substrates with a Mild Sulfenium Carrier Azobenzene‐2‐sulfenyl Bromide. Issue 52 (24th December 2013) - Ahmed, Nizamuddin; Bhattacharjee, Tirtha; Barman, Pranjit; Bhattacharjee, Saibal Kanti
Abstract Mild reaction conditions, simple work‐up, good yields and short reaction times make this method a convenient and practical alternative to existing methods.